Compatibility of Recycling Plastic Lubricants - Grigorov, Andrey; Ponomarenko, Vitaliy; Slepuzhnikov, Yevhen; Bondarenko, Oleksandr; Artemev, Sergey; Ilinskyi, Oleksii; Bryhada, Olena (My University, 2023)
The compatibility of recycled greases thickened with 5 % (wt.) polyethylene and polypropylene solid waste was studied. It was found that according to the values of the dropping point and adhesive properties, recycled greases, regardless of the base oil and thickener, are compatible. However, when 10 % (mass) of recycled lubricants are added to Solidol "Zh", its adhesion properties deteriorate by 300-400 rpm, due to the negative effect of the aging products of base oils on its structure, which indicates their incompatibility.
Keywords: compatibility; grease; dropping point; adhesive properties; polymer thickener; base oil; thermal degradation